2014
DOI: 10.1002/acr.22297
|View full text |Cite
|
Sign up to set email alerts
|

Milk Consumption and Progression of Medial Tibiofemoral Knee Osteoarthritis: Data From the Osteoarthritis Initiative

Abstract: Objectives: Milk consumption has long been recognized for its important role in bone health, but its role in the progression of knee osteoarthritis (OA) is unclear. We examine the prospective association of milk consumption with radiographic progression of knee OA. Methods: In the Osteoarthritis Initiative, 2,148 participants (3,064 knees) with radiographic knee OA and having dietary data at baseline were followed up to 12, 24, 36 and 48 months. The milk consumption was assessed with a Block Brief Food Frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
3
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 36 publications
0
34
3
1
Order By: Relevance
“…Some studies [45,46,49,64,66▪,97▪,102] have highlighted interactions among these risk factors (mostly surrounding sex differences in other osteoarthritis risk factors); given the multifactorial nature of osteoarthritis, future research should carefully consider these interrelationships. Also important is the existence of multiple known modifiable or preventable risk factors for osteoarthritis incidence and/or progression (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies [45,46,49,64,66▪,97▪,102] have highlighted interactions among these risk factors (mostly surrounding sex differences in other osteoarthritis risk factors); given the multifactorial nature of osteoarthritis, future research should carefully consider these interrelationships. Also important is the existence of multiple known modifiable or preventable risk factors for osteoarthritis incidence and/or progression (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Among Osteoarthritis Initiative (OAI) participants, greater baseline milk intake was associated with less joint space narrowing over 4 years among women [46]. Previous studies of vitamin D and osteoarthritis have been conflicting [11,12], and a clinical trial showed no effect of vitamin D supplementation on knee cartilage loss [47].…”
Section: Person-level Risk Factorsmentioning
confidence: 99%
“…Vitamin C was not significantly associated with knee symptoms in OA, and the results for vitamin D were inconclusive 40 . Mediterranean diet was associated with lower WOMAC scores and better quality of life 41 , and higher milk consumption was linked to reduced radiographic OA progression in women 42 . Interestingly, milk-based dietary supplements have also been shown to reduce OA pain symptoms in two randomized clinical trials 43,44 .…”
Section: Discussionmentioning
confidence: 96%
“…Many of the epidemiological researchers for osteoarthritis have considered various predictors and associated morbidities involved with osteoarthritis. It has been associated with body mass index [5], low Vitamin D [6,7], and increased consumption of soft drinks in men [8] and in women with limited milk consumption [9], not breastfeeding [10], and giving birth [10]. Inconclusive and contradictory associations have been reported concerning associations of osteoarthritis and sex in which some researchers found positive associations [7,11,12] while others did not [13] and with smoking in which some researchers found positive associations [14], others found protective associations [15,16], and others did not find any association [13].…”
Section: Introductionmentioning
confidence: 99%